Western-Icelanders, past and present : Icelandic identity among late-generation ethnics in Canada - Arnbjörg Jónsdóttir 1987- (2016)
Canada is a multicultural country composed of more than 200 ethnicities, including Icelandic-Canadians. About 15.000 Icelanders are believed to have emigrated from Iceland to Canada and the USA in the period 1870 to 1914. The largest group of Icelandic settlers formed the colony New Iceland in the Interlake region of Manitoba. Icelanders refer to Icelandic Canadians and Icelandic Americans as Western-Icelanders. This thesis focuses on how Canadian descendants of the Icelandic settlers see and experience themselves in relation to their Icelandic heritage. The main research questions are whether an Icelandic ethnic identity is present among late-generation ethnics; when and among whom the Icelandic ethnic identity is strongest and most present; and whether this identity might have something in common with the historical experiences of the early Western-Icelanders. Semi-structured interviews were conducted with six individuals who are of Icelandic descent and represent the present and future, while the past Icelandic-Canadian community experiences are presented in letters which Jón Jónsson’s, the researchers´ great-great grandfather, wrote and sent to Aðalbjörg Jónsdóttir, the researcher´s great-grandmother. Herbert J. Gans’ terms and definitions regarding ethnic identity, including his theories concerning termination of the European identities in North America, were used as guideline for this research. The research findings indicate that an Icelandic ethnic identity is present among all of the interviewees and that significant associations can be found in comparing their experiences with the practices, views and testimonies expressed in Jón Jónsson´s letters. Furthermore, only one of the informants can be viewed as having entered the last, terminal stage of Icelandic ethnic identity.